Kampung Kweel Sebagai Basis Pengembangan Tanaman Sagu (Metroxylon sp.) Di Kabupaten Merauke: Pengabdian - Susanti, Diana S; Mekiuw, Yosehi; Maturbongs, Modestha R; Suryadi, Suryadi; Kusumah, Rangga (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Sago is a food commodity that is widely consumed by local Papuans, including in Merauke Regency. Sago plants can be processed by local people into papeda, grilled sago and other traditional foods. The area of ​​sago planting is currently starting to decrease due to land conversion into oil palm plantations and housing. This can cause sago plants to be threatened with extinction. Therefore, through the partner village development program (PDM), the activity implementation team proposed the development of sago plants in Merauke Regency through Kweel Village. The implementation of activities includes counseling with a participatory system and conducting demonstration plots of plant cultivation. The activities carried out are; 1) Providing counseling on the benefits of the importance of sago cultivation, 2) Providing assistance in sago cultivation. The assistance activities of Kweel Village became the basis for the development of sago land with counseling and FGD activities, that the community has great enthusiasm. With information related to the development of sago land, it becomes an attraction and increases community knowledge. So that the Kweel village opened 1 Ha of Sago land as a pilot area, with the hope that it will continue to develop sago land that has been agreed upon for the lands that become Sago cultivation areas.